1987
DOI: 10.1121/1.394633
|View full text |Cite
|
Sign up to set email alerts
|

A frequency importance function for continuous discourse

Abstract: Normal hearing subjects estimated the intelligibility of continuous discourse (CD) passages spoken by three talkers (two male and one female) under 135 conditions of filtering and signal-to-noise ratio. The relationship between the intelligibility of CD and the articulation index (the transfer function) was different from any found in ANSI S3.5-1969. Also, the lower frequencies were found to be relatively more important for the intelligibility of CD than for identification of nonsense syllables and other types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
76
2
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 0 publications
5
76
2
1
Order By: Relevance
“…The use of bandpass filtering demonstrated that different spectral ranges were employed for each of the forms: one form usually corresponded to a band of frequencies below 1500 Hz and the other to a band of frequencies above 1500 Hz. Interestingly, there is considerable evidence that a frequency of approximately 1500 ± 300 Hz (depending on stimuli and procedures) divides speech into highpass and low-pass ranges of equal intelligibility (Beranek, 1947;Fletcher & Galt, 1950;Hirsh, Reynolds, & Joseph, 1954;Pollack & Pickett, 1964;Studebaker, Pavlovic, & Sherbecoe, 1987). Sentences provide higher intelligibility scores than do word lists, and each of two nonoverlapping spectral ranges can be quite intelligible when heard alone.…”
Section: Resultsmentioning
confidence: 99%
“…The use of bandpass filtering demonstrated that different spectral ranges were employed for each of the forms: one form usually corresponded to a band of frequencies below 1500 Hz and the other to a band of frequencies above 1500 Hz. Interestingly, there is considerable evidence that a frequency of approximately 1500 ± 300 Hz (depending on stimuli and procedures) divides speech into highpass and low-pass ranges of equal intelligibility (Beranek, 1947;Fletcher & Galt, 1950;Hirsh, Reynolds, & Joseph, 1954;Pollack & Pickett, 1964;Studebaker, Pavlovic, & Sherbecoe, 1987). Sentences provide higher intelligibility scores than do word lists, and each of two nonoverlapping spectral ranges can be quite intelligible when heard alone.…”
Section: Resultsmentioning
confidence: 99%
“…In order to be able to predict the speech intelligibility under such masking conditions, French and Steinberg ͑1947͒, Fletcher and Galt ͑1950͒, and later Kryter ͑1962a, b͒ initiated a calculation scheme, known as the Articulation Index ͑AI͒, which at present still is used by a number of investigators ͑Rankovic, 1998investigators ͑Rankovic, , 2002Hogan and Turner, 1998;Müsch and Buus, 2001;Turner and Henry, 2002;Dubno et al, 2002, 2003͒. In 1984, Pavlovic and others ͑Dirks et al, 1986Kamm et al, 1985;Pavlovic and Studebaker, 1984;Pavlovic et al, 1986;Studebaker et al, 1987 started to re-examine the AI calculation scheme, which has led to a new method accepted as the ANSI S3.5-1997 ͑1997͒. Since its revision in 1997, the method is named the Speech Intelligibility Index ͑SII͒.…”
Section: Introductionmentioning
confidence: 99%
“…frequencies, it was necessary to add masking noise to further degrade these signals so that intelligibility would vary with cutoff changes (see Studebaker, Pavlovic, & Sherbecoe, 1987). Pavlovic (1994) summarized some of this recent work and listed 1/3-octave band importance functions for a variety of speech materials, including sentences, short passages, and average speech.…”
mentioning
confidence: 99%